A 52-week safety study in cynomolgus macaques for genetically modified rice expressing Cry1Ab/1Ac protein. (September 2016) - Mao, Jie; Sun, Xing; Cheng, Jian-Hua; Shi, Yong-Jie; Wang, Xin-Zheng; Qin, Jun-Jie; Sang, Zhi-Hong; He, Kun; Xia, Qing
Abstract: A 52-week feeding study in cynomolgus macaques was carried out to evaluate the safety of Bt rice Huahui 1 (HH1), a transgenic rice line expressing Cry1Ab/1Ac protein. Monkeys were fed a diet with 20% or 60% HH1 rice, 20% or 60% parental rice (Minghui 63, MH63), normal diet, normal diet spiked with purified recombinant Cry1Ab/1Ac fusion protein or bovine serum albumin (BSA) respectively. During the feeding trail, clinical observations were conducted daily, and multiple parameters, including body weight, body temperature, electrocardiogram, hematology, blood biochemistry, serum metabolome and gut microbiome were examined at regular intervals. Upon sacrifice, the organs were weighted, and the macroscopic, microscopic and electron microscopic examinations were performed. The results show no adverse or toxic effects of Bt rice HH1 or Cry1Ab/1Ac fusion protein on monkeys. Therefore, the present 52-week primate feeding study suggests that the transgenic rice containing Cry 1Ab/1Ac is equivalent to its parental rice line MH63. Highlights: A 52-week feeding study of Bt rice expressing Cry1Ab/1Ac was conducted in macaques. No adverse effect was observed in the monkeys consumed Bt rice. GM diet feeding had no significant effects on monkey gut microbiome and serum metabonome. Bt rice HH1 is equivalent to its parental rice line MH63.